FAKTOR - FAKTOR YANG MEMPENGARUHI PERILAKU MENABUNG DI KALANGAN MAHASISWA UNIVERSITAS PANCA SAKTI BEKASI PRODI PENDIDIKAN EKONOMI ANGKATAN 2021 - Aliza Mulbaidah Deka (Arthaniti Studies, 2026)
Financial management is the responsibility of each individual towards their finances because it is related to the fulfillment of daily needs. One of the efforts in financial management is to foster the habit of saving behavior. Students are one part of the community groups in Indonesia. Students have a high consumerist nature because for some of them saving behavior is not an easy thing to do.